Younger women have a better prognosis among patients with esophageal squamous cell carcinoma after esophagectomy - Su, Xiao-Dong; Zhang, Xu; Xie, Hao-Jun; Lin, Peng; Zhang, Lanjun; Rong, Tiehua (Journal of Thoracic Disease, 2016)
Background: Epidemiological studies have suggested a potential role for sex hormones in esophageal squamous cell carcinoma (ESCC) etiology. However, the significance of gender as an independent prognostic factor remains uncertain. Our retrospective study was designed to investigate the prognostic role of gender for survival after esophagectomy. Methods: Data from 674 patients with ESCC who underwent surgical resection were retrospectively analysed. Age 55 years was selected as a surrogate for menopause. Patients were assigned to age-gender groups: A (female younger than age 55 years), B (female age 55 years and older), C (male younger than age 55 years) and D (male age 55 years and older). Univariate and multivariate analyses were performed to identify prognostic factors for survival. Results: There were 520 males and 154 females with median age was 58 years. The 1-, 3-, 5-year survival rates of group A, B, C and D were 93.6%, 70.2%, 61.7% vs. 86.9%, 47.7%, 40.2% vs. 77.8%, 43.9%, 37.0% and 80.3%, 47.9%, 36.6%, respectively (P=0.003). Multivariate analysis suggested that age-gender groups and pTNM staging were independent prognostic factors. Conclusions: Among patients with ESCC after esophagectomy, women younger than age 55 years attained a favorable prognosis.